The Emerging Passion Fruit Industry in Florida - Ellen Garcia; Ali Sarkhosh; Tie Liu (EDIS, 2023)
Tropical fruits are in high demand for their unique flavor, aroma, and their functional composition of phytochemicals with physiological benefits, deeming them “nutraceuticals.” Passion fruit can potentially be of high economic value for Florida because of its suitability for tropical climates and its nutrient density, which has great benefits for human health. Passion fruit contains robust and essential vitamins and minerals such as vitamin A, vitamin C, riboflavin, niacin, iron, potassium, zinc, and magnesium (Pham-Huy et al. 2008). This publication can help consumers understand passion fruit appeal and help Floridian producers and marketers understand the competitive advantages of passion fruit as an emerging industry for Florida.